1990
DOI: 10.1002/ajh.2830350204
|View full text |Cite
|
Sign up to set email alerts
|

Detection of interleukin‐6 (IL‐6) in human bone marrow myeloma cells by light and electron microscopy

Abstract: We used an Avidin-Biotin peroxidase complex (ABC) immunoperoxidase technique to evaluate the localization of IL-6 of human bone marrow cells in multiple myeloma (MM). The cellular distribution of IL-6 was determined at light and electron microscopic levels. The author's study indicated that cytoplasmic IL-6 was detected only in the myeloma cells of bone marrow cells. Immunoelectron microscopic (immuno-EM) study showed positive reactivity mainly in the perinuclear space (PNS), well-developed rough endoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Since the same proportions of cells expressed both the IL‐6 mRNA and protein, these observations support the suggestion that malignant plasma cells are an important source of IL‐6 in vivo . Immunolocalization of IL‐6 protein has also been observed by Ohtake et al (1990 ) in plasma cells from three patients with MM using an avidin/biotin immunoperoxidase technique. However, myeloma cells were identified on the basis of morphology alone and no specific markers were used.…”
Section: Discussionmentioning
confidence: 81%
“…Since the same proportions of cells expressed both the IL‐6 mRNA and protein, these observations support the suggestion that malignant plasma cells are an important source of IL‐6 in vivo . Immunolocalization of IL‐6 protein has also been observed by Ohtake et al (1990 ) in plasma cells from three patients with MM using an avidin/biotin immunoperoxidase technique. However, myeloma cells were identified on the basis of morphology alone and no specific markers were used.…”
Section: Discussionmentioning
confidence: 81%
“…Freeman et al demonstrated that four of four myelomas and plasma cell leukemias expressed IL-6 mRNA [79]. Cytoplasmic IL-6 was detected in myeloma cells of the bone marrow by light and electron microscopy [80]. It was reported that the growth-inducing activity of IL-1 or TNF on freshly isolated myeloma cells could be due to an IL-6-mediated autocrine mechanism, because anti-IL-6 antibody completely inhibited IL-1-induced myeloma growth [81].…”
Section: Il-6 Is a Growth Factor For Plasmacytoma/myelomamentioning
confidence: 99%